Transcutaneous auricular vagus nerve stimulation as an innovative approach for managing perioperative gastrointestinal dysfunction: a narrative review - Zhang, Ling; Zhang, Qin; Yin, Xuefeng; Cao, Ya; Chen, Ye; Li, Zhonghua; Shen, Yu; Fan, Keyu; Liu, Mingxia; Qian, Lu; Wang, Yunfeng; Dai, Chongchun; et al. (Frontiers in Medicine, 2025)
Postoperative gastrointestinal dysfunction (POGD) is a prevalent and clinically significant complication following surgical procedures. It adversely impacts patient comfort, prolongs postoperative hospitalization duration, and increases the risk of perioperative complications and unplanned readmissions, thereby contributing to higher healthcare costs. Transcutaneous auricular vagus nerve stimulation (taVNS) has emerged as a promising neuromodulatory intervention. As a non-invasive technique, it offers several advantages, including ease of administration, a favorable safety profile, and high patient acceptability. This narrative review outlines the pathophysiological mechanisms underlying POGD, the anatomical basis of the vagus nerve, the technical parameters of taVNS, and its therapeutic mechanisms in managing postoperative gastrointestinal disturbances. The objective is to support the development of a comprehensive treatment approach for patients with POGD, promoting accelerated recovery.